Development of E-Commerce Based on Business to Consumers to Increase Sales of Queen Fashion Products During Covid-19 Pandemic in Sragen - Harsono, H; Widayat, Adhelia Zulfa (Proceedings International Conference on Education Innovation and Social Science, 2022)
Business to consumers based e-commerce is a business carried out between business people and consumers. ECommerce is part of e-business, where the scope of e-business is wider, not just commerce but also includes collaborating with business partners, customer service, job vacancies etc. This study aims to describe the development of e-commerce in increasing sales of Queen Fashion products through promotion. This study uses a qualitative research method with an ethnographic approach. The object of this research is the owner, employee and customer of Queen fashion. Data collection techniques used in this study were interviews, observation, and documentation. Research sources include owners, employees and customer of Queen fashion. Data were analyzed using qualitative data analysis techniques, generally subjective. In conclusion, promotion through e-commerce with the existing marketplace in Queen fashion, can expand the marketing of Queen fashion products to outside the Sragen Regency area, and can be accessed quickly. With this e-commerce can make it easier for consumers to order, choose products, transactions and others. E-Commerce has a very good impact on sales of Queen fashion products, this is based on sales and orders.